Building a Better Quaternary Ammonium Compound (QAC): Branched Tetracationic Antiseptic Amphiphiles. (1st June 2016) - Forman, Megan E.; Jennings, Megan C.; Wuest, William M.; Minbiole, Kevin P. C.
Abstract: Bacteria contaminate surfaces in a wide variety of environments, causing severe problems across a number of industries. In a continuation of our campaign to develop novel antibacterial quaternary ammonium compounds (QACs) as useful antiseptics, we have identified a starting material bearing four tertiary amines, enabling the rapid synthesis of several tris‐ and tetracationic QACs. Herein we report the synthesis and biological activity of a series of 24 multiQACs deemed the "superT" family, and an investigation of the role of cationic charge in antimicrobial and anti‐biofilm activity, as well as toxicity. This class represents the most potent series of QACs reported to date against methicillin‐resistant Staphylococcus aureus (MRSA), with minimum inhibitory concentrations (MICs) and minimum biofilm eradication concentrations (MBECs) as low as 0.25 and 25 μm, respectively. Based on the significant cell‐surface‐charge differences between bacterial and eukaryotic cells, in certain cases we observed excellent efficacy‐to‐toxicity profiles, exceeding a 100‐fold differential. This work further elucidates the chemical underpinnings of disinfectant efficacy versus toxicity based on cationic charge. Abstract : "SuperT" QACs : Disinfectants must have two key features: potent activity against a variety of microorganisms, and minimal toxicity to eukaryotic cells. How do we design nonspecific antibacterial agents that kill bacteria, yet are safe enough to use in households, hospitals, and industry? This work examines the role of charge and spacing in developing novel antiseptics with desirable efficacy to toxicity profiles.